Revisiting student attrition studies: a new conceptual perspective - Had Sabtu, Helminiry; Wan Mohd Noor, Wan Shakizah; Mohd Isa, Mohd Faizal (Universiti Teknologi Malaysia, 2016)
This article focuses on the overview of the student attrition model as well as related theory that are pertinent to student attrition studies. It comprises an investigation into the prominent student attrition models, such as the Undergraduate Dropout Process Model presented by Spady, and Tinto’s Model of Institutional Departure.Then, the focus is on the work by Bean that resulted in the Student Attrition Model, and the Pascarella produced the Conceptual Model for Research on Student-Faculty Informal Contact, as well as an exploration of attrition studies in Malaysian Higher Education.In addition, an initial conceptual research model derived from existing prominent student attrition models was proposed by the researchers for investigation in Malaysian Technical and Vocational Education and Training (TVET) student attrition studies, as well as for academic student attrition studies.